An innovative electronically-conducting matrix of the cathode for sodium sulfur battery - Kim, Seong In; Park, Won Il; Jung, Keeyoung; Kim, Chang-Sam (ELSEVIER SCIENCE BV, 2016)
An innovative electronically-conducting cathode matrix, that makes sodium sulfur (NaS) battery excellent in discharge-charge performance, is prepared by surface modification of a carbon felt with inorganic nanoparticles. A carbon felt is dipped into an inorganic-organic hybrid sol, dried, and heat-treated at 600 degrees C for 2 h in a flowing argon. Coated surface of the felt has been examined by scanning electron microscopy (SEM) equipped with energy dispersive X-ray spectroscopy (EDX) and scanning transmission electron microscopy (STEM). The cell prepared with the coated carbon felt shows 92% of charge acceptance and 99.9% of coulombic efficiency at 100 mA cm(-2) of current density. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: POLYCRYSTALLINE; BETA' ' -ALUMINA; ELECTRODE